Involvement of HLADQA1*05 in Patients with Inflammatory Bowel Disease Treated with Anti-TNF Drugs - Anna Pau; Ilaria Galliano; Elisa Barnini; Maddalena Dini; Antonio Pizzol; Alice Ponte; Stefano Gambarino; Pier Luigi Calvo; Massimiliano Bergallo (Medicina)
Background: Over the past decade, TNF inhibitors such as Infliximab and Adalimumab have become central to Inflammatory Bowel Diseases treatment, greatly enhancing patient outcomes. However, immunogenicity—where anti-drug antibodies diminish effectiveness—remains an issue, often requiring dose changes or combination therapies. Pharmacogenomics is increasingly applied in IBD to personalise treatment, especially since genetic factors like the HLA-DQA1*05 variant heighten the immunogenicity risk with IFX. This study aims to examine the relationship between the HLA-DQA1*05 variant and response loss or antibody development in patients regularly monitored on IFX or ADA. Methods: Sixty-five paediatric IBD patients were enrolled, with therapeutic drug monitoring (TDM) of IFX and ADA, conducted using immunoenzymatic assays. The presence of the HLA-DQA1*05 T>C allele variant was also tested using a Biomole HLA-DQA1 Real-time PCR kit. Results: The HLA-DQA1*05 rs2097432 T>C allele was present in 54% of patients on IFX and 69% of those on ADA. No statistically significant differences were found between HLA carriers and non-carriers across any of the three analysed groups: IFX, ADA and the overall anti-TNFα. Conclusions: Our study suggests that the HLA-DQA1*05 allele does not increase the risk of secondary loss of response to anti-TNF therapy, likely because most patients were on a combination of anti-TNF agents and immunomodulators, which can lower anti-drug antibody production. Testing for HLA-DQA105 can aid in personalising treatment and optimising therapy to minimise immunogenicity risks.